Exosomal circular RNA hsa_circ_0006220, and hsa_circ_0001666 as biomarkers in the diagnosis of pancreatic cancer. Issue 6 (21st April 2022) - Hong, Lu; Xu, Liu; Jin, Lufei; Xu, Kaiwei; Tang, Weiwei; Zhu, Yuchao; Qiu, Xuedan; Wang, Jianhua
Abstract: Background: Pancreatic cancer is a highly malignant tumor of the digestive system. Objective: Exosomal circular RNA can be used as a biomarker for the early diagnosis of pancreatic cancer. Methods: The expression of various differentially expressed circRNAs in pancreatic cancer tissues was analyzed by gene chip, exosome expression was verified by electron microscopy and Western blotting, and the expression of exosomal circRNA in pancreatic cancer cells, tissues, and plasma were determined by quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR). Results: Compared with healthy controls, hsa_circ_0006220 and hsa_circ_0001666 were highly expressed in exosomes in the plasma of pancreatic cancer patients. The AUC values were 0.7817 for hsa_circ_0006220, 0.8062 for hsa_circ_0001666, and 0.884 for the combined diagnosis. In addition, clinicopathological features revealed that the expression of hsa_circ_0006220 in plasma exosomes from pancreatic cancer patients was associated with CA19‐9 levels ( p = 0.0001) and lymph node metastasis ( p = 0.0005). The expression of hsa_circ_0001666 was correlated with both tumor size ( p = 0.0157) and CA19‐9 level ( p = 0.0001). Conclusions: The high expression of exosomal hsa_circ_0001666 and hsa_circ_0006220 suggests that these can be used as new biomarkers for the diagnosis and treatment of pancreatic cancer. Abstract : Pancreatic cancer is a highly malignant tumor of the digestive system. Exosomal circular RNA can be used as a biomarker for the early diagnosis of pancreatic cancer. The expression of various differentially expressed circRNAs in pancreatic cancer tissues was analyzed by gene chip, exosome expression was verified by electron microscopy and Western blotting, and the expression of exosomal circRNA in pancreatic cancer cells, tissues, and plasma were determined by quantitative reverse transcription PCR (qRT‐PCR). Exosomes hsa_circ_0001666 and hsa_circ_0006220 were highly expressed in pancreatic cancer tissues, cell lines, and plasma samples of pancreatic cancer patients and were related to clinical staging. The high expression of exosomal hsa_circ_0001666 and hsa_circ_000622 suggests that these can be used as new biomarkers for the diagnosis and treatment of pancreatic cancer.